Activated, Pro-Inflammatory Th1, Th17, and Memory CD4+ T Cells and B Cells Are Involved in Delayed-Type Hypersensitivity Arthritis (DTHA) Inflammation and Paw Swelling in Mice - Li, Gaoyang; Kolan, Shrikant Shantilal; Guo, Shuai; Marciniak, Katarzyna; Kolan, Pratibha; Malachin, Giulia; Grimolizzi, Franco; Haraldsen, Guttorm; Skålhegg, Bjørn Steen (Frontiers in Immunology, 2021)
Delayed-type hypersensitivity arthritis (DTHA) is a recently established experimental model of rheumatoid arthritis (RA) in mice with pharmacological value. Despite an indispensable role for CD4+ T cells in inducing DTHA, a potential role for CD4+ T cell subsets is lacking. Here we have quantified CD4+ subsets during DTHA development and found that levels of activated-, pro-inflammatory Th1-, Th17- and memory- CD4+ T cells in draining lymph nodes were increased with differential dynamic patterns after DTHA induction. Moreover, according to B cell depletion experiments, it has been suggested that this cell type is not involved in DTHA. We show that DTHA is associated with increased levels of B cells in draining lymph nodes accompanied by increased levels of circulating IgG. Finally, using the anti-rheumatoid agents, methotrexate (MTX) and the anti-inflammatory drug dexamethasone (DEX), we showed that MTX and DEX differentially suppressed DTHA-induced paw swelling and inflammation. The effects of MTX and DEX coincided with differential regulation of levels of Th1, Th17 and memory T cells as well as B cells. Our results implicate Th1, Th17 and memory T cells, together with activated B cells to be involved and required for DTHA-induced paw swelling and inflammation.